NATO AND CENTRAL ASIAN STATES: THE PROSPECTS OF COOPERATION - A. M. Akmataliyeva (Сравнительная политика)
Although cooperation between NATO and Central Asian countries dates back to the 1990s, significant presence of the Alliance in the region is visible throughout the last decade only. The cooperation advanced due to the NATO-led operation in Afghanistan. However, its planned conclusion in 2012 will not lead to the withdrawal of the Alliance from Central Asia. Throughout the last decade NATO developed a network of diversified partnerships with countries of the region. In this process Kazakhstan emerged as its most promising and active partner.